Working More, Less or the Same During COVID-19? A Mixed Method, Intersectional Analysis of Remote Workers. Issue 2 (May 2022) - Fan, Wen; Moen, Phyllis
The COVID-19 pandemic has transformed where paid work is done. Workers able to do so have been required to work remotely. We draw on survey data collected in October 2020 from a nationally representative sample of 3, 017 remote workers, as well as qualitative survey data collected from 231 remote workers, to examine perceived changes in work hours from before to during the pandemic. Results indicate women are at greater risk of change (either a major decrease or a major increase)—rather than stability—in work hours. Gender also intersects with caregiving, race/ethnicity, prior remote work experiences, and socioeconomic status to shape changes in hours. Women and men in the sandwich generation, as well as women (but not men) with pre-school children, are the most likely to report a decrease in work hours, whereas women with older children at home or caring for adults (but not both) are the most likely to have an increase in hours. Remote working Black women and women moving into remote work are more likely to experience a major increase in hours worked, even as Hispanic women and Black men are the most likely to report somewhat of a reduction in work hours. Gender also intersects with SES, such that women without a college degree are more likely to have a decrease in work hours, while women with an advanced degree and women managers report a considerable increase in work hours. Qualitative data further illuminate why work hours change or remain stable for remote workers during COVID-19.